New long-horned caddisfly genus and species of Leptoceridae (Insecta: Trichoptera) from Brazil - Henriques-Oliveira, Ana Lucia; Silva, Andre Luís Ramos; Nessimian, Jorge Luiz; Takiya, Daniela Maeda (Zootaxa, 2021)
Ibyacerina caparao new genus, new species (Trichoptera: Leptoceridae) is described and illustrated from specimens collected at Serra do Caparaó, Minas Gerais, Brazil. The monotypic genus is characterized by tibial spur formula 0,2,2; preanal appendages originating from a single base with a median process; tergum X broad, heavily sclerotized, saddle-like, wider at apex, and upturned, bearing small stout setae; inferior appendages each 3-branched, setose; and phallic apparatus tubular, curved slightly ventrad, with pair of lateral processes. Phylogenetic Bayesian and maximum likelihood analyses based on concatenated cytochrome oxidase I (COI) and carbamoyl-phosphate synthetase (CAD) partial sequences (1,504 bp) including representatives of 38 leptocerid genera positioned Ibyacerina gen. nov. with good support within Leptocerinae. However, due to low branch support of most relationships among genera within the clade of Leptocerinae, except Mystacidini, Setodini, and Leptocerini, its close affinities and tribal placement are still unknown.